Factors Affecting Repurchase Intention on Lazada in DKI Jakarta - Safira, Putri; Indriyanti, Irma; Souisa, Johanis (Universitas Semarang, 2023)
The purpose of this research is to identify and analyze the effect of trust, perceived risk, reference group, behavior control awareness, usefulness and convenient and business competency to repurchase intention on Lazada consumers in DKI Jakarta. The form of research used is descriptive research and causality research, in which variables are measured by 5 point likert scale. This research used data collected by questionnaires with non-probability sampling technique and purposive sampling method and used 102 respondents. Processed with statistic program and statistical method is multiple regression. The results on this research indicate that the variables of trust, reference group, behavior control awareness and business competency have a positive effect to repurchase intention, which is supported in previous studies. But, the variables perceived risk and usefulness and convenient have no effect to repurchase intention.